Interpolation with Specified Error of a Point Series Belonging to a Monotone Curve - Havrylenko, Yevhen; Гавриленко, Євген Андрійович; Гавриленко, Евгений Андреевич; Kholodniak, Yuliia; Холодняк, Юлія Володимирівна; Холодняк, Юлия Владимировна; Halko, Serhii; Галько, Сергій Віталійович; Галько, Сергей Витальевич; Vershkov, Oleksandr; Вершков, Олександр Олександрович; Вершков, Александр Александрович; et al. (My University, 2021)
The paper addresses the problem of modeling a smooth contour interpolating a point series belonging to a curve containing no special points, which represents the original curve with specified accuracy. The contour is formed within the area of possible location of the parts of the interpolated curve along which the curvature values are monotonously increased or decreased. The absolute interpolation error of the point series is estimated by the width of the area of possible location of the curve. As a result of assigning each intermediate point, the location of two new sections of the curve that lie within the area of the corresponding output section is obtained. When the interpolation error becomes less than the given value, the area of location of the curve is considered to be formed, and the resulting point series is interpolated by a contour that lies within the area. The possibility to shape the contours with arcs of circles specified by characteristics is investigated.
Keywords: monotone curve; tangent circle; adjacent circle; area of location of the curve; contour